Analisis Kesulitan Pembelajaran Bahasa Inggris Siswa Kelas V SDN Babarsari Tahun Ajaran 2024/2025 - Tyas Purnawati (Lembaga Yasin AlSys, 2025)
English language learning at the elementary school level continues to face various challenges, particularly in vocabulary acquisition, which serves as a foundational element for language skills such as listening, speaking, reading, and writing. This study aims to analyze English learning difficulties among fifth-grade students at SDN Babarsari in the 2024/2025 academic year, focusing on vocabulary mastery and sentence structure. A qualitative descriptive method was employed, grounded in Vygotsky’s sociocultural theory, especially the concepts of the Zone of Proximal Development (ZPD) and scaffolding. Data were collected through reading tests, classroom observations, and documentation of learning outcomes from 57 students. The results show that 52.6% of students experienced difficulties understanding vocabulary meanings, 8.8% struggled with sentence construction, and 8.8% faced challenges memorizing vocabulary. Contributing factors included cognitive, affective, and memory aspects, learning strategies, and limited learning environments. The study concludes that English learning at the elementary level should be designed collaboratively, contextually, and based on social interaction. The application of scaffolding aligned with students’ ZPD proved effective in bridging language competence gaps. The research implications emphasize the importance of adaptive teaching strategies, such as using visual media, group discussions, and peer teaching. Theoretically, this study reinforces the social-cognitive approach in English language learning and recommends further research with a broader scope and exploration of digital technology utilization.